EVALUATION OF THE EARLY INTERVENTION PROGRAM FOR ARI IN TODDLERS TO SUPPORT THE SDG's HEALTH TARGETS AT THE PRIMARY SERVICE LEVEL IN GORONTALO REGENCY - Yanti Hano; Dewi Kartika; Mayangsari Kau; Ririn Pakaya; Maesarah Maesarah (Universitas Negeri Gorontalo, 2026)
Acute Respiratory Infection (ARI) remains one of the leading causes of morbidity and mortality in toddlers in Indonesia. Based on data from the Ministry of Health, the prevalence of ARI in the last three years has shown a fluctuating trend. In 2022, approximately 8.5% of the total population experienced ARI, this figure increased to 9.2% in 2023, and decreased slightly to 8.8% in 2024. This study aims to evaluate the implementation of the early intervention program for ARI in toddlers in primary health care facilities using the CIPP (Context, Input, Process, Product) evaluation model, as a comprehensive approach to assess the program and its contribution to achieving SDG’s target 3.2. The research method uses a mixed approach (mixed methods) with data collection through surveys, in-depth interviews, and FGDs. Respondents consisted of health workers, cadres, and parents of toddlers in Gorontalo Regency. The results of the study showed that in the general context, early intervention programs for ISPA according to regional needs. From the perspective of input, there are limitations in human resources, infrastructure, and suboptimal budget support. The program implementation process has been ongoing through early detection, community education, and standardized procedures, but still faces obstacles in monitoring and reporting. The program has contributed to reducing ISPA cases in toddlers, although achieving the SDG targets still requires strengthening prevention and program sustainability. Overall, the study results indicate that the ISPA early intervention program has a good initial foundation, but needs to be strengthened through ongoing education to achieve SDG target 3.2, namely reducing infant mortality due to preventable diseases.